The Role of Activating Transcription Factor 4 (ATF4) in the Physiological Response to Dietary Sulfur Amino Acid Restriction (OR27-01-19). (13th June 2019) - Jonsson, William; Margolies, Nicholas; Mirek, Emily; Gettys, Thomas; Anthony, Tracy
Abstract: Objectives: Dietary restriction of the sulfur amino acids (SAAs) improves metabolic health in part via hepatic production of fibroblast growth factor 21 (FGF21). Transcriptional control of Fgf21 includes regulation by ATF4 during low protein feeding. Therefore, we aimed to determine the impact of Atf4 deletion on FGF21 levels and associated metabolic outcomes in mice fed a SAA restricted diet. Methods: Male and female mice lacking Atf4 globally or in hepatocytes only were fed either a SAA restricted diet (0.17% Met, 0% Cys) or a control diet (0.86% Met, 0% Cys) alongside littermate controls for up to 10 wk. Body mass and composition, energy expenditure and intake were measured. Blood and tissues were collected at specific time points. Transcript (RT-qPCR) and protein (ELISA and Western blot) abundances were analyzed by two factor ANOVA or Kruskal-Wallis Test, with alpha = 0.05. Results: Independent of genotype, SAA restriction attenuated weight gain and reduced adiposity despite increased food intake. Improvements in body weight and composition strongly associated with increased energy expenditure regardless of genotype. Deletion of Atf4 did not prevent hepatic Fgf21 nor circulating FGF21 from increasing during chronic SAA restriction ( P  < 0.05, effect of diet). However, loss of hepatic Atf4 prevented increased circulating FGF21 at 12 h. Overall, males fed the SAA restricted diet induced hepatic Fgf21 and serum FGF21 to a greater degree than females. Other known ATF4 targets in liver such as asparagine synthetase, Asns, showed significant induction in the livers of only intact SAA restricted mice. Conversely, loss of Atf4 exacerbated induction of the pro-apoptotic transcription factor Chop ( P  < 0.05) by SAA restriction. Conclusions: Genetic loss of Atf4 delays but does not impede FGF21 production during dietary SAA restriction. Biological sex is a contributing factor to some of the physiological responses to dietary SAA restriction. Funding Sources: DK109714 (TGA) and DK096311 (TWG).